Improving the effectiveness of psychological interventions for depression and anxiety in the cardiac rehabilitation pathway using group-based metacognitive therapy (PATHWAY Group MCT): Study protocol for a randomised controlled trial - Wells, A.; McNicol, K.; Reeves, D.; Salmon, P.; Davies, L.; Heagerty, A.; Doherty, P.; McPhillips, R.; Anderson, Rebecca; Faija, C.; Capobianco, L.; Morley, H.; et al. (BioMed Central, 2018)
Background: Anxiety and depression are prevalent among cardiac rehabilitation patients but pharmacological and psychological treatments have limited effectiveness in this group. Furthermore, psychological interventions have not been systematically integrated into cardiac rehabilitation services despite being a strategic priority for the UK National Health Service. A promising new treatment, metacognitive therapy, may be well-suited to the needs of cardiac rehabilitation patients and has the potential to improve outcomes. It is based on the metacognitive model, which proposes that a thinking style dominated by rumination, worry and threat monitoring maintains emotional distress. Metacognitive therapy is highly effective at reducing this thinking style and alleviating anxiety and depression in mental health settings. This trial aims to evaluate the effectiveness and cost-effectiveness of group-based metacognitive therapy for cardiac rehabilitation patients with elevated anxiety and/or depressive symptoms. Methods/Design: The PATHWAY Group-MCT trial is a multicentre, two-arm, single-blind, randomised controlled trial comparing the clinical- and cost-effectiveness of group-based metacognitive therapy plus usual cardiac rehabilitation to usual cardiac rehabilitation alone. Cardiac rehabilitation patients (target sample n = 332) with elevated anxiety and/or depressive symptoms will be recruited across five UK National Health Service Trusts. Participants randomised to the intervention arm will receive six weekly sessions of group-based metacognitive therapy delivered by either cardiac rehabilitation professionals or research nurses. The intervention and control groups will both be offered the usual cardiac rehabilitation programme within their Trust. The primary outcome is severity of anxiety and depressive symptoms at 4-month follow-up measured by the Hospital Anxiety and Depression Scale total score. Secondary outcomes are severity of anxiety/depression at 12-month follow-up, health-related quality of life, severity of post-traumatic stress symptoms and strength of metacognitive beliefs at 4- and 12-month follow-up. Qualitative interviews will help to develop an account of barriers and enablers to the effectiveness of the intervention. Discussion: This trial will evaluate the effectiveness and cost-effectiveness of group-based metacognitive therapy in alleviating anxiety and depression in cardiac rehabilitation patients. The therapy, if effective, offers the potential to improve psychological wellbeing and quality of life in this large group of patients.